Audit as a tool for reducing compliance risks of digital investment ecosystem participants - V. A. Yakimova (Интеллект. Инновации. Инвестиции, 2023)
The article is devoted to the problem of developing mechanisms to increase the sustainability of the digital investment ecosystem, in which the main participants are investors, borrowers or other persons attracting investments, the Bank of Russia as a regulator, a professional organization. The purpose of this study is to identify ways to trust the system of digital investment platforms by developing financial compliance methods for ecosystem participants. In the course of the study, methods of statistical analysis, generalization and grouping of compliance risk assessment, ecosystem modeling with the allocation of functions and actions of its participants were used. The ecosystem approach was used as a basic approach, which allows revealing interactions and assessing the impact of the risks of one participant on the stability of the ecosystem as a whole. The study found that participants are exposed to high compliance risks that can lead to a system default and cause systemic risks of a chain of bankruptcies due to defaults, changes in rules and restrictions. The level of compliance risk for crowdfunding participants was 27%, and the analysis of operators’ declarations identifies 23 types of risks that an investor takes on and which carry the threat of loss of invested capital. High risks and their diversification led to the conclusion that it is necessary to build investment compliance control procedures into the investment ecosystem, which can be carried out by audit organizations as assurance tasks. The results of the study are of practical importance for the development of the methodological apparatus of compliance in the process of carrying out activities by audit organizations and the development of a system for regulating the activities of investment ecosystems by the Bank of Russia.